Potency To Recycle Hydrapulper Reject Waste Of Paper Mill Into Composite Particleboard - Andri Taufick Rizaluddin; Yusup Setiawan (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2019)
Solid waste of paper mill hydrapulper reject (HR) has a relatively high plastic content, with around 45-49% composition of the total HR. About 99% of the plastic has the catagory of High Density Polyethylene (HDPE). HDPE is a type of Polyethylene (PE) plastic which has high recyclability and may be reformed at high temperature. This study tries to discribe the potential of producing particleboards derived from HR using a hot-press method. Molded HR was being hot-pressed at a presssure of 25 kgf/cm2for 5 – 15 minutes of residence time, with a variation of of the amount of HR from 150-500 gram, and variations in hot-press temperature of 150-180°C. The resulting product is then analyzed for parameters of moisture content, density, water absorption, thickness swelling, and internal bond compared to SNI 03-2105-2006 and JIS A 5908-2003. The results showed that most of the samples were relatively accepted to the SNI. The best results are obtained at HR weight of 250 gram with 165 and 180°C pressing temperature, and pressing time more than 10 minutes. The addition of HDPE pellets shows an increment of density and decrement of moisture content of particleboard, while the addition of MA shows some decrements of moisture content and water absoption of particleboard.